Analysis of the stress state in non-axially symmetrical cold forging dies - Killmann, Martin; Merklein, Marion (Procedia Manufacturing, 2020)
Conventionally, reinforcement systems are used to decrease tensile stresses in axially symmetrical cold forging dies. The increasing complexity of parts due to lightweight design leading to higher functional integration causes the necessity of producing non-axially symmetrical parts, for which there is insufficient knowledge about the adequate application of reinforcement systems. To gain understanding about the stress distribution for non-axially symmetrical dies, a cold forging process for producing elliptical parts is introduced and numerically described. The simulation model is validated in a test set up with strain gauges, which are used to measure the strains on the die and reinforcement ring. Subsequently, the process is analysed regarding the location, direction and magnitude of the resulting prestresses and maximum stresses. Based on the findings, a classification of areas for non-circular symmetrical cold forging tools is introduced. The compressive area is subjected to increasingly high contact pressures by the workpiece. This leads to compressive radial stresses and radial displacements. The high displacements induce a bending effect, which causes tangential stresses in the tensile area. The gained process understanding is used to propose measures for improving the stress state in cold forging dies for asymmetrical parts by locally strengthening the reinforcement syste
Keywords: Cold Forming; Forging; Die Load; Asymmetrical Tools; Reinforcement Systems